Infections in newly diagnosed Spanish patients with systemic lupus erythematosus: data from the RELES cohort. (December 2018) - González-Echavarri, C; Capdevila, O; Espinosa, G; Suárez, S; Marín-Ballvé, A; González-León, R; Rodríguez-Carballeira, M; Fonseca-Aizpuru, E; Pinilla, B; Pallarés, L; Ruiz-Irastorza, G; ,
Objectives: Using data of patients from the inception cohort Registro Español de Lupus Eritematoso Sistémico (RELES), we aimed to analyse the incidence of severe infection in the first two years of follow-up and how predictors of infection change during the course of systemic lupus erythematosus (SLE). Material and methods: The study included 282 patients. Markers of lupus activity, prednisone doses and immunosuppressive therapy were compared between patients with and without infections in the first and second year of the disease. Drug therapy administered during the first month of follow-up has been considered as a potential predictor of infections during the first year and medications administered during the first year have been considered potential predictors of infections during the second. Results: Nineteen patients (6.4%) had a documented episode of major infection during the first year of follow-up and 16 patients (5.67%) during the second. The following variables were associated with infections during the first year: hypocomplementaemia at diagnosis ( p  < 0.01), nephritis at diagnosis ( p  = 0.03), SLEDAI score ( p  < 0.01), prednisone >30 mg/day ( p  = 0.01), methylprednisolone pulses ( p  = 0.05) and mycophenolate use ( p  = 0.02). The independent variables in the final model were hypocomplementaemia (odds ratio (OR) 4.41, 95% confidence interval (CI) 0.96–20.20, p  = 0.05) and a dose of prednisone >30 mg/day (OR 6.60, 95% CI 1.34–32.42, p  = 0.02). The following variables were associated with infections during the second year: dose of prednisone > 7.5 mg/day ( p  = 0.05), methylprednisolone pulses ( p  = 0.07), duration of therapy with antimalarials ( p  = 0.09), therapy with mycophenolate ( p  = 0.01), therapy with cyclophosphamide ( p  = 0.05). The independent variables in the final model were a dose of prednisone >7.5 mg/day (OR 4.52, 95% CI 0.99–21, p  = 0.054) and duration of therapy with antimalarials as a protective factor (OR 0.99, 95% CI 0.99–1.00, p  = 0.053). Conclusions: The low incidence of early infections in the RELES cohort is partially explained by the extended use of antimalarials and by the general avoidance of prolonged high doses of prednisone. Patients with high baseline activity are at a higher risk of infection during the first months but therapy with medium–high doses of prednisone is the main predictor of infectious events. Thus, every effort should be made to limit oral glucocorticoid use from the very beginning of the SLE course.